Search for excited B+c states - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; et al. (Journal of high energy physics, 2018)
A search is performed in the invariant mass spectrum of the B c + π+π− system for the excited B c + states B c (21S0)+ and B c (23S1)+ using a data sample of pp collisions collected by the LHCb experiment at the centre-of-mass energy of s√=8s=8 \sqrt{s}=8 TeV, corresponding to an integrated luminosity of 2 fb−1. No evidence is seen for either state. Upper limits on the ratios of the production cross-sections of the B c (21S0)+ and B c (23S1)+ states times the branching fractions of B c (21S0)+ → B c + π+π− and B c (23S1)+ → B c * +π+π− over the production cross-section of the B c + state are given as a function of their masses. They are found to be between 0.02 and 0.14 at 95% confidence level for B c (21S0)+ and B c (23S1)+ in the mass ranges [6830, 6890] MeV/c2 and [6795, 6890] MeV/c2, respectively. Open image in new window
Im Titel sind "+" und "c" untereinander geschrieben: "+" hochgestellt, "c" tiefgestellt
The LHCb collaboration: R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, M. Dziewiecki, S. Esen, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere] (LHCb collaboration)
Gesehen am 04.06.2019